(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The stock market is a multifunctional system that contributes to: accumulation of capital for investment in the production and social spheres; structural reorganization of the economy; positive dynamics of the social structure of society; improving the welfare of citizens, due to the ownership and free disposal of securities. The Russian Federation’s full-scale war with Ukraine, which has lasted for more than a year and a half, has brought Ukraine large-scale financial and economic instability, which is manifested in the deterioration of the socio-economic condition and the deterioration of the state of the financial system, regarding its performance of its functions. The purpose of the article is to understand the processes of development and analysis the main trends of the current state and to identify the problems of the functioning of the stock market of Ukraine under martial. The results. The main ways of attracting funds on the stock market are: 1) covering the shortage of money for financing activities; 2) restarting and modernization of existing capacities; 3) replenishment of working capital, restructuring of indebtedness; 4) development of core activities and maintenance of production level; 5) development of innovative projects and diversification of activities; 6) creation of an enterprise, subsidiary companies and structural units; 7) development of financial infrastructure; 8) formation of exchange history. During the studied period, the stock market in Ukraine consisted only of DGB, the rest of the instruments were small deals that did not have a significant impact on liquidity. In order to restore Ukraine in the post-war period, business development requires the involvement of additional sources of financing. Therefore, planning and preparing new financing mechanisms today will increase the chances of success on the stock market. Among the main problems that have arisen acutely on the way to the recovery and development of the stock market are: insufficient legislative regulation; low liquidity (in the event of a crisis situation on the stock market, as well as when investors wish to sell their own securities, the market is unable to fully absorb the volume being sold, as a result, sellers significantly reduce prices and the market falls; lack of new financial instruments (a low share of shares the stock market of Ukraine in the pre-war period and the dominance of bonds in the conditions of military aggression). Conclusions. The main priorities for the development of the Ukrainian stock market are: - the creation of an appropriate legal framework that will regulate the rights and obligations of all participants in the stock market and ensure the creation of an appropriate system for the protection the rights of investors and securities owners; - integration of the domestic stock market into international financial markets; - the development of the stock market infrastructure and the development of a wide range of tools, the availability of effective mechanisms for the interaction market participants; - formation of a new infrastructure of the stock market (a new model) that meets the norms of the international market; development of financial market segments (banking, insurance, pension sector, etc.); - increasing the investment literacy of the population.